Viva Vigan! (Vigan Tourism Council, 2000)
Documentary on the history of the foundation of Vigan, featuring its Heritage Village, churches and its status as a World Heritage Site. Aside from monumental structures, its pre-colonial crafts and industries - pottery, hand-weaving, wood furniture-making and tile-making - are highlighted.